Pengaruh Content Marketing dan Influencer Marketing melalui Tiktok terhadap Keputusan Pembelian Produk Hanaka & Co pada Generasi Z - Komang Widya Sari Dewi Sudiarta; I Nengah Wirsa (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to determine the effect of content marketing and influencer marketing through TikTok on purchasing decisions of Hanaka & Co products among Generation Z in Denpasar City. This research used a quantitative approach with an associative research design. The population in this study consisted of Generation Z in Denpasar City who use TikTok and have been exposed to Hanaka & Co marketing content. The sampling technique used purposive sampling with a total of 100 respondents. Data were collected through online questionnaires using a Likert scale of 1–5. The data analysis technique used multiple linear regression analysis with the assistance of SPSS software. The results showed that content marketing had a positive and significant effect on purchasing decisions with a significance value of 0.000. Influencer marketing also had a positive and significant effect on purchasing decisions with a significance value of 0.000. Simultaneously, content marketing and influencer marketing significantly influenced purchasing decisions of Hanaka & Co products among Generation Z in Denpasar City.